Current and future management of non-tuberculous mycobacterial pulmonary disease (NTM-PD) in the UK. Issue 1 (21st June 2020) - Lipman, Marc; Cleverley, Joanne; Fardon, Tom; Musaddaq, Besma; Peckham, Daniel; van der Laan, Roald; Whitaker, Paul; White, Jacqui
Abstract : A rising number of non-tuberculous mycobacterial (NTM) isolates are being identified in UK clinical practice. There are many uncertainties around the management of non-tuberculous mycobacterial pulmonary disease (NTM-PD), including its epidemiology, diagnosis, treatment and prevention. Regional variations in how patients with NTM-PD are managed reflects the lack of standardised pathways in the UK. Service optimisation and multidisciplinary working can improve the quality of care for patients with NTM-PD, including (1) better identification of patients at risk of NTM-PD and modification of risk factors where applicable; (2) standardisation of reference laboratory testing to offer clinicians access to accurate and prompt information on NTM species and drug sensitivities; (3) development of recognised specialist NTM nursing care; (4) standardisation of NTM-PD imaging strategies for monitoring of treatment and disease progression; (5) establishment of a hub-and-spoke model of care, including clear referral and management pathways, dedicated NTM-PD multidisciplinary teams, and long-term patient follow-up; (6) formation of clinical networks to link experts who manage diseases associated with NTM; (7) enabling patients to access relevant support groups that can provide information and support for their condition; and (8) development of NTM research groups to allow patient participation in clinical trials and to facilitate professional education.